Breakthrough Invasive Candidiasis in Patients on Micafungin - Pfeiffer, Christopher D. (2010)
For Candida species, a bimodal wild-type MIC distribution for echinocandins exists, but resistance to echinocandins is rare. We characterized isolates from patients with invasive candidiasis (IC) breaking through ≥3 doses of micafungin therapy during the first 28 months of its use at our center: MICs were determined and hot-spot regions within FKS genes were sequenced. Eleven of 12 breakthrough IC cases identified were in transplant recipients. The median duration of micafungin exposure prior to breakthrough was 33 days (range, 5 to 165). Seventeen breakthrough isolates were recovered: FKS hot-spot mutations were found in 5 C. glabrata and 2 C. tropicalis isolates; of these, 5 (including all C. glabrata isolates) had micafungin MICs of >2 μg/ml, but all demonstrated caspofungin MICs of >2 μg/ml. Five C. parapsilosis isolates had wild-type FKS sequences and caspofungin MICs of 0.5 to 1 μg/ml, but 4/5 had micafungin MICs of >2 μg/ml. The remaining isolates retained echinocandin MICs of ≤2 μg/ml and wild-type FKS gene sequences. Breakthrough IC on micafungin treatment occurred predominantly in severely immunosuppressed patients with heavy prior micafungin exposure. The majority of cases were due to C. glabrata with an FKS mutation or wild-type C. parapsilosis with elevated micafungin MICs. MIC testing with caspofungin identified all mutant strains. Whether the naturally occurring polymorphism within the C. parapsilosis FKS1 gene responsible for the bimodal wild-type MIC distribution is also responsible for micafungin MICs of >2 μg/ml and clinical breakthrough or an alternative mechanism contributes to the nonsusceptible echinocandin MICs in C. parapsilosis requires further study.